Publicity or impact? The use of crowdfunding by Indonesian social media influencers during the covid-19 pandemic - Nissa Cita Adinia; Mediana Hanifa (Journal of Social Studies (JSS), 2022)
Indonesia is marching toward tackling challenges during the endless Covid-19 pandemic. Under a situation known as VUCA (volatile, uncertain, complex, and ambiguous), a troop of social media influencers (SMI) paved the way to create crowdfunding initiatives. Shedding from the discussion of disaster capitalism, where individual or entities make profit from large-scale crises, also take advantage of the destabilized atmosphere, this paper analyses the initiatives of three Indonesian social media influencers in raising funds through Kitabisa.com from March to November 2020. Under the hashtag #BersamaLawanCorona (together fight the corona), the biggest crowdfunding platform, Kitabisa.com has gathered more than 158 billion rupiahs (11,2 million USD) taken from 5.655 campaigns during March to November 2020 period. These efforts are mainly pioneered by SMIs and their followers. Combining desk review and social media analysis method, the paper revealed that the crowdfunding initiatives by SMIs portrayed two sides of a coin: on the one hand reflects the emergence of solidarity and social contribution to create a positive impact, and on the other, generates publicity. It is, however, too quick to conclude whether the initiatives reflect a practice of disaster capitalism, because the publicity that they generated for these crowdfunding initiatives were not higher compare to publicity they gained from their everyday content.